Culture and the Death of God, by Terry Eagleton. Yale University Press, 2014. 234pp., hb. £18.99. ISBN-13: 9780300203998. (28th September 2017) - Howes, Graham
Abstract : Culture and the Death of God, by Terry Eagleton. Yale University Press, 2014. 234pp., hb. £18.99. ISBN-13: 9780300203998.